HST observations of [O III] emission in nearby QSO2s: Physical properties of the outflows. Issue Volume 15:Issue S359(2020) (March 2019) - Falcao, Anna Trindade; Kraemer, S. B.; Fischer, T. C.; Crenshaw, D. M.; Revalski, M.; Schmitt, H. R.
Abstract: We used Space Telescope Imaging Spectrograph (STIS) long slit medium-resolution G430M and G750M spectra to analyze the extended [O III] λ5007 emission in a sample of twelve QSO2s from Reyes et al . (2008 ). The purpose of the study was to determine the properties of the mass outflows and their role in AGN feedback. We measured fluxes and velocities as functions of deprojected radial distances. Using photoionization models and ionizing luminosities derived from [O III], we were able to estimate the densities for the emission-line gas. From these results, we derived masses, mass outflow rates, kinetic energies and kinetic luminosity rates as a function of radial distance for each of the targets. Masses are several times 10 3 - 10 7 solar masses, which are comparable to values determined from a recent photoionization study of Mrk 34 (Revalski). Additionally, we are studying the possible role of X-ray winds in these QSO2s.